(untitled) (Global Journals of Research in Engineering, 2012)
The slipper bearing is an integrated part of an axial piston pump. Proper lubrication is important for successful operation of the slipper bearing. This type of bearing is a type of hydrostatic thrust bearing. Many works have been done in the recent past on this type of bearing. This current work is based on the theoretical investigation of the locus of the load centre of this type of bearing. The leakage losses and the slipper drag are two important factors on which this type of bearing is designed. The load carrying capacity has a direct impact on those two factors. On the other hand the stability of the bearing depends upon the position of the load centre. There are many input factors on which the position of load centre is varied. These input factors thus play an important role on the smooth operation of such bearing. Such input variable are slipper tilt, applied pressure on the slipper, slipper speed, slipper non flatness angle or slipper land size. On the variation of these input variables, the nature of the position of load centre is plotted in this work. Based on the results the reasonable conclusions are made.